THE EFFECT OF GROUP INVESTIGATION (GI) MODEL AND LEARNING STYLE TOWARD STUDENTS’ ECONOMICS ENGLISH SPEAKING COMPETENCE OF PROF. DR. HAZAIRIN, SH UNIVERSITY - Melati Melati (Edu-Ling: Journal of English Education and Linguistics, 2017)
ABSTRACT This study was designed: (1) to find out a significant progress on the English speaking skill of students’ Economics using Internet reading materials. (2) to find out a significant effect by using visual and auditory learning style toward English Speaking Skill. (3) to know an interaction effect between Group Investigation Model and learning style toward English speaking skill. Quasi-experimental research 2 x 2 factorial design used in this research, and all the computational procedure were run by using SPSS. The results showed that, 1) there was a significant progress of students’ Englsih Speaking skill after given Group Investigation Model, 2) there was the effect of learning style to the students’ English speaking skills, 3) there was an interaction effect between the use of Group Investigation Model to the reading materials from the multimedia and learning styles on speaking competence.